2023
DOI: 10.24912/jmieb.v7i1.21043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Internal Locus of Control on Ethical Behavior With Work-Life Balance as Moderating Variable

Ida Ayu Nirma Prameswari,
Desak Made Mya Yudia Sari

Abstract: Perilaku etis yaitu sikap dan tindakan seseorang yang cocok dengan norma-norma sosial di masyarakat umum karena berhubungan dengan perbuatan yang baik, benar, memberi manfaat dan tidak merugikan. Perilaku etis auditor dapat mempengaruhi kepercayaan dan kredibilitas publik. Oleh karena itu, auditor dalam menjalankan tugasnya harus mematuhi etika yang berlaku dan mampu mengendalikan dirinya agar terhindar dari masalah yang berkaitan dengan perilaku tidak etis. Penelitian ini dilakukan guna mengetahui kemampuan w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The second hypothesis further results Internal locus of control rules Employee Performance; H2 accepted. Internal locus of control is a perspective that all results obtained are due to capacity actions and factors in themselves (Berger & Haywood, 2016;Prameswari & Sari, 2023). The results of the study descriptively found an locus of control indicator with the statement, "I believe that if I want to succeed, I must do something".…”
Section: Discussionmentioning
confidence: 85%
“…The second hypothesis further results Internal locus of control rules Employee Performance; H2 accepted. Internal locus of control is a perspective that all results obtained are due to capacity actions and factors in themselves (Berger & Haywood, 2016;Prameswari & Sari, 2023). The results of the study descriptively found an locus of control indicator with the statement, "I believe that if I want to succeed, I must do something".…”
Section: Discussionmentioning
confidence: 85%